Explicit and implied significance of contemporary public spaces. Part 1. Spaces of attractions - Dziubiński , Dariusz (Budownictwo i Architektura / Civil and Architectural Engineering, 2020)
This text presents considerations encouraged by thoughts and conclusions gained from research on several beach bars and their comparison with other urban public spaces, run in Wrocław from 2018 to 2019. The similarities and differences between the two types of spaces provoke a question about the meaning of what we call „public spaces” today. The question is also asked, somewhat perversely, about the validity of following best practices based on proxemic principles and focused on attracting and retaining people in urban spaces. The paper examines not so much the rules but the purpose, in other words the type of space we receive/can achieve as a result of applying these principles, since people in the urban space (private or public) are only guests, while their choice is reduced to the top-down offer. The above doubt also results from the conclusion regarding the most important feature determining attractiveness of a beach bar space, which in my opinion, is the freedom of behaviour for users. In it we can see deficiencies of the prevailing narrative about our participation in space and, above all, the possibility of choice, or what should be called the limitations of choice – the lack of possession/self-agency. Such a situation, largely conditioned by politics (and economics), reduces public space to the role of a “space of attractions” (curiosities), whose action and participation is based on experiencing – on a direct experience. The clash of these two forces – standardization and individualization, erodes the current model of common spaces based on the historical (nineteenth century) one, whose images are transferred only in the form of empty clichés. Thus, the limitation of choices, the need to fall into line and appearances of a community lead to an escape upwards – enclaves for the chosen ones (omnitopia) and downwards – niches for the rebellious ones (heterotopia), while beach bars represent both ways of escape. Against this background, the purposefulness of expert/ top-down creation of public spaces, carried out in isolation from other essential values and laws, appears problematic.